Scurvy: A Disease not to be Forgotten. (23rd December 2020) - Montalto, Massimo; Porceddu, Enrica; Pero, Erika; Lupascu, Andrea; Gallo, Antonella; De Simone, Clara; Nucera, Eleonora; Aruanno, Arianna; Giarretta, Igor; Pola, Roberto; Landolfi, Raffaele
Abstract: An 18‐year‐old man presented to our hospital with muscular pain, diffuse petechiae, spontaneous thigh ecchymosis, edema and pain of the right knee, bilateral pretibial subcutaneous nodules, and gingival hypertrophy and hemorrhage. His history was positive for a mixed anxiety‐depressive disorder and a restrictive diet caused by self‐diagnosed food allergies. Skin lesions appeared like hyperkeratotic papules with coiled hairs and perifollicular hemorrhages. A diagnosis of scurvy was made upon demonstration of low serum levels of ascorbic acid. An allergy evaluation found cross‐reactivity between pollens and food, related to the presence of panallergens. Moreover, we found that our patient was also affected by celiac disease. In conclusion, scurvy should be considered in the differential diagnosis of patients with petechiae and ecchymosis, especially when food restriction, malabsorption, or psychiatric disorders are present.